AH-35 Potence for Osteogenesis of (Cissus quadrangularis Salisb) Ekstract in Ovariectomized Rats - Mustafa Sabri; Nurhidayat Nurhidayat; Wasmen Manalu; Bambang Pontjo Priosoeryanto; Hamny Hamny; Sri Wahyuni (Media Veteriner, 2015)
Potence for Osteogenesis of (Cissus quadrangularis Salisb) Ekstract in Ovariectomized Rats